TEKNIK, METODE, DAN IDEOLOGI PENERJEMAHAN DALAM TERJEMAHAN BUKU RISĀLAH ILĀ SYABĀBIL-UMMAH - Nur Eko Ikhsanto, Abdul Malik (CMES (Center of Middle Eastern Studies), 2016)
This research analyzes technique, method and ideology of translation in translating the book of Risa@lah ila@ Syaba@bil-Ummah. It is aimed to (1) describe the technique of translation applied in translating words, phrases, clauses,and sentences contained in the book, (2) identify the method and ideology that tends to be used by translator to translate the book. The method used in this research is qualitative descriptive. The data sources are the book ofRisa@lah ila@ Syaba@bil-Ummah and its translation in Bahasa Indonesia entitled Menjadi Pemuda Peka Zaman (MPPZ). Data collected through reading books RSU and MPPZ as a whole to obtain an overview and classify existing translation techniques. Data analysis was carried out in stages; First, classifying the translation techniques of words, phrases, clauses, and sentencesfrom the text of RSU into MPPZ. Second, looking at the application of translation techniques to define translation methods used.Third, analyzing translation methods to interpret translation ideologies tend to be used by the translator. The results showed that there are 17 kinds of translation techniques used by the translator from totally 356 ones happened in 150 data. They are; addition (76), inversion (49), deletion (42), borrowing pure (33), modulation (28), compensation (22), naturalborrowing (21), transposition (18), calque (18), adaptation (15), amplification (13), literaltranslation (11), discursive creation (6), established equivalence (1), particularization (1), generalization (1), description (1). The most frequently tehcnique appliedis the addition one. This was done to ensure the easiness for readers to understand the message. Based on the dominant technique appeared, the book is likely to use the communicative method and domestication ideology, shown by 76.7% of techniques are tend to target language (Bahasa Indonesia) while 23.7% are tend to source language (Arabic).a@